2005
DOI: 10.1111/j.1525-1594.2005.29073.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Muscle Growth and Tissue Changes Induced by Electrical Stimulation of Denervated Degenerated Muscles With CT and Stereolithographic 3D Modeling

Abstract: In the frame of the EU-funded RISE project, patients with lower motor neuron lesion and denervated and degenerated muscles are treated with electrical stimulation, with the aim of restoring muscle mass and force. Spiral computer tomography from the hip joint down to the knee joint is used to gather three-dimensional data on the upper leg tissue. These data are analyzed in order to monitor tissue changes induced by the electrical stimulation treatment. Especially the data representing muscle tissue and bone tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 1 publication
0
26
0
1
Order By: Relevance
“…Other experimental stimulation studies have not shown any improvement of mass or force (Dow et al, 2006). In humans with spinal cord injury, studies using spiral CT have shown promising results from electrical stimulation of denervated muscle (Helgason et al, 2005). There has been a paucity of electrical stimulation studies on humans with peripheral nerve injury (Eberstein and Eberstein, 1996).…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…Other experimental stimulation studies have not shown any improvement of mass or force (Dow et al, 2006). In humans with spinal cord injury, studies using spiral CT have shown promising results from electrical stimulation of denervated muscle (Helgason et al, 2005). There has been a paucity of electrical stimulation studies on humans with peripheral nerve injury (Eberstein and Eberstein, 1996).…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…It was also widely believed that FES was unsuitable in DDMtraining. Kern, however, not only showed that DDM patients can indeed be trained with FES using surfaceelectrodes, but also that FES training is able to restore the ability of muscles to perform tetanic contractions, that, in fact, are essential to prevent/recover atrophy by loading the muscles [23, 41,42,43]. The crucial indicator for the therapy is, of course, muscle growth.…”
Section: Table 3 Remarkable Clinical Occurrences For Patient 3 Which mentioning
confidence: 99%
“…The rectus femoris muscle was segmented and a three dimensional (3D) computer model constructed. This was then used to track the tissue changes as therapy progressed [2,3]. After the project period the patient have not been stimulating or only very sporadically.…”
Section: Introductionmentioning
confidence: 99%
“…A SCI at the level of Th12 and L1 often result in a complete flaccid paralysis of the muscle of the thigh. To stop the degeneration or even built up volume and force of the muscles they can be treated with electrical stimulation [1,2]. Since there is no lower motor neuron the muscle fibres have to be stimulated directly demanding electrical pulses of two order of magnitude higher energy as those for nerve stimulation [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation